Known and Unknown Identities: Openness and Identity as Experienced by Adult Adoptees. Issue 2 (3rd April 2019) - Henze-Pedersen, Sofie
Abstract: This qualitative study investigates the relationship between openness and identity among 15 adoptees. Several studies have argued that a high degree of openness is important for the identity of adoptees. However, few have explored this relationship. Two types of openness (biographical knowledge and communicative openness) are used to categorize the empirical material, making it possible to shed light on how different types of openness influence identity. The findings suggest that there is no direct link between a high degree of openness and positive identity formation. Rather, the relationship appears to be situational and changeable as adoptees come of age.